How to Retain Your Best Faculty Members - Jeff Buller (Academic Chairpersons Conference Proceedings, 2023)
As department chairs, we devote a great deal of time and energy to recruiting excellent faculty members, but we spend far less time and energy trying to retain them. Superb college professors are vital to a department’s success, but they are also highly competitive in the marketplace. They have options and, if they begin to think that they can do better (financially or otherwise) elsewhere or even outside of academia, they’ll start looking elsewhere. In this best practices workshop, we’ll explore how to apply certain strategies to our work at the departmental level so as to increase the likelihood that more of our best faculty members will choose to remain with us.
Keywords: faculty; retention; orientation; on boarding; engagement